The Intercultural Reading Course at Majapahit Islamic University: an Analysis of Teachers' Practices - Annavidza, Qonita; Lindawati, Rini; Ganinda, Nurhayati (PT. Kreasi Karya Majakata, 2024)
Teaching practice plays a crucial role in successful learning. Previous research indicates that low student performance is often not solely due to a lack of content understanding but is also significantly influenced by teachers' practices during the learning process. Intercultural understanding is recognized as a key component of English language proficiency. This research explores how teachers the teachers’ practices while teaching intercultural reading course. This study employs a qualitative descriptive approach. The research examines the entire process of intercultural reading instruction in the fourth semester, from initial preparation to post-reading activities. This includes the preparation of materials, reading texts, and the methods of delivery and interaction used by teachers. The findings are based on four observation sessions and an interview with one teacher and two students. The study reveals that teachers provide texts, asked the students to answer related questions, and encourage them to develop critical thinking by connecting newly acquired cultural knowledge with their own experiences. The teaching practices emphasize active discussions and questioning the reading content to enhance students' reading skills while deepening their cross-cultural understanding.